2017
DOI: 10.1007/s00709-017-1194-9
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis of muskmelon (Cucumis melo L.) and genetic stability assessment of regenerants using flow cytometry and ISSR markers

Abstract: A new protocol for in vitro regeneration through direct somatic embryogenesis for two muskmelon cultivars (Cucumis melo L., "Mashhadi" and "Eivanaki") is reported. Somatic embryos were obtained culturing 4- and 8-day-old cotyledons, seeds, and hypocotyls on Murashige and Skoog medium supplemented with three different hormonal combinations never tested so far for melon (naphthoxyacetic acid (NOA) + thidiazuron (TDZ), NOA + 6-banzylaminopurine (BAP), and 2,4-dichlorophenoxyacetic acid (2,4-D) + N-(2-chloro-4-pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 60 publications
3
26
1
Order By: Relevance
“…SCoT markers were already reported for assessing the genetic stability of several plant species such as Cleome gynandra [53], Pittosporum eriocarpum [48] , Albizia julibrissin [54], and Simmondsia chinensis [55]. Similarly, ISSR primer based assessment of regenerans was reported in Tylophora indica [56], Simmondsia chinensis [57], Rauwolfia tetraphylla L. [58], Spilanthes calva [59], Cucumis melo L. [60], Cornus alba [61], and Zea mays [62].…”
Section: Resultsmentioning
confidence: 99%
“…SCoT markers were already reported for assessing the genetic stability of several plant species such as Cleome gynandra [53], Pittosporum eriocarpum [48] , Albizia julibrissin [54], and Simmondsia chinensis [55]. Similarly, ISSR primer based assessment of regenerans was reported in Tylophora indica [56], Simmondsia chinensis [57], Rauwolfia tetraphylla L. [58], Spilanthes calva [59], Cucumis melo L. [60], Cornus alba [61], and Zea mays [62].…”
Section: Resultsmentioning
confidence: 99%
“…Molecular analyses and flow cytometry have been used in many species to evaluate the trueness-to-type of plantlets regenerated via somatic embryogenesis. These species include olives (Brada€ ı et al, 2016), muskmelon (Raji et al, 2018), chrysanthemum (Lema-Rumi nska and Sliwi nska, 2015), ajowan (Niazian et al, 2017), Italian grapevine (Carra et al, 2016), Anthurium andraeanum (Bhattacharya et al, 2016), citrus species (Meziane et al, 2017), and Cassia occidentalis (Naz et al, 2016). In walnut, RFLP and isozyme analysis were used to determine the origin of SEs by Aly et al (1992).…”
mentioning
confidence: 99%
“…Molecular markers commonly used for the evaluation of somaclonal variation include randomly amplified polymorphic DNA (RAPD), restricted fragment length polymorphism (RFLP), simple sequence repeats (SSRs), and ISSR. Of these, ISSR is the fastest, simplest, and most powerful (Raji et al, 2018).…”
mentioning
confidence: 99%
“…Many studies on in vitro propagation have focused on optimal conditions for morphogenesis; however, conditions that are optimal for plant regeneration may not be optimal for maintenance of genetic integrity (Nehra et al 1992). Some studies conducted with SE induction have reported ≥ 90 % genetic integrity, with little influence of type and concentration of PGR or length of time in culture (Harvengt et al 2001, Lopes et al 2006, Yang et al 2008, Marum et al 2009, Carloni et al 2014, Li et al 2014, Carra et al 2016, Naz et al 2016, Niazian et al 2017, Raji et al 2018. In contrast, there are also reports of high genetic variation: in Picea mariana, a phenotypic variation of 11 -57 % was reported and was associated with genotype and length in culture (Tremblay et al 1999).…”
Section: Introductionmentioning
confidence: 99%